Performance Evaluation and Comparison of Two Cascaded Configurations of PV Generators-Five Levels Inverter for a Stand-Alone Application in South Algeria - Karima Benamrane; Tarak Benslimane; Othmane Abdelkhalek; Thameur Abdelkrim; Abdelhalim Borni (Institute of Advanced Engineering and Science, 2017)
In this paper two configurations of solar photovoltaic energy conversion using the NPC five levels inverter for stand-alone application in south Algeria are proposed and their performances compared. The first cascade uses four separate PV sources and the second configuration use only one PV generator. In these two cases and without DC/DC converter introduced between PV source and inverter and to get a stable AC voltage, authors in propose a proportional regulator of inverter modulation index. The SVPWM technique is used in order to get the best voltage waveform. For the second configuration proposed, we introduce in the control loops another algorithm which uses the redundant vectors of space vector diagram of inverter to stabilise the DC bus voltages. A real data of temperature and solar irradiation obtained by radiometric station in Ghardaïa city in south Algeria are used to test the performance of proposed controls. The simulation results show that the inverter output voltage is stable for the two configurations proposed despite the variation of solar irradiation, temperature and load. Also, the THD obtained is in the limits of international standards. Then, the PV cascade with separate PV sources is the best solution, seeing that we do not need to use another algorithm in the control loops.